Prognostic Value of Coexisting Lobular Carcinoma In Situ With Invasive Lobular Carcinoma. Issue 10 (November 2016) - Harbhajanka, Aparna; Lamzabi, Ihab; Syed, Sahr; Jain, Richa; Ghai, Ritu; Reddy, Vijaya B.; Bitterman, Pincas; Gattuso, Paolo
Abstract : Aims and Objectives: Recent studies show that lobular carcinoma in situ (LCIS) and invasive lobular carcinoma (ILC) share similar genetic molecular biology. There are increasing concerns regarding the biological significance of LCIS. The aim of this study is to investigate whether the presence of coexisting LCIS in ILC affects tumor biology and behavior and to correlate it with other clinicopathologic parameters. Materials and Methods: In this study, 254 cases of ILC were included. Clinicopathologic parameters and immunohistochemical stains for estrogen receptor (ER), progesterone receptor (PR), E-cadherin, human epidermal growth factor receptor (HER2), and MIB-1 of 254 ILC cases were retrieved. The patient with ILC and coexisting LCIS were compared with pure ILC cases with respect to different clinicopathologic parameters. Results: Of the 254 cases, 107 cases were pure ILC and 147 cases were ILC with coexisting LCIS. Seventy-six (76/184, 41.32%) cases showed axillary lymph node metastases. Lymph node metastasis was absent in 108 cases, micrometastasis was present in 5 cases, and stage N1, N2, N3 in 51, 5, and 15 cases, respectively. Nodal involvement, locoregional and distant recurrence of ILC with LCIS were less frequent compared with ILC without LCIS with P -value of 0.034 and 0.007, respectively. The presence of coexisting LCIS in ILC predicted higher disease-free survival (DFS) compared with pure ILC ( P =0.034, log-rank test). When divided into different strata, ER-positive ILC cases with associated LCIS cases showed better DFS than ER-positive pure ILC cases ( P =0.021, log-rank test). Similarly, ILC cases with LCIS in patient less than 50 years showed better DFS than the patient less than 50 years with pure ILC ( P =0.045, log-rank test). Conclusions: In conclusion, ILC coexisting with lobular carcinoma in situ (ILC+LCIS) is characterized by less nodal involvement, lower locoregional, and distant recurrence and better DFS than pure ILC. When divided into different strata, ER-positive and less than 50-year groups with ILC+LCIS show even significant better DFS than pure ILC. These findings suggest that there is biological significance of coexisting LCIS in ILC and that this may have more effect on tumor aggressiveness in certain strata of ILC.